Utilization of Polymeric Micelles as a Lucrative Platform for Efficient Brain Deposition of Olanzapine as an Antischizophrenic Drug via Intranasal Delivery - Hadel A. Abo El-Enin; Marwa F. Ahmed; Ibrahim A. Naguib; Shaymaa W. El-Far; Mohammed M. Ghoneim; Izzeddin Alsalahat; Hend Mohamed Abdel-Bar (MDPI AG, 2022)
Schizophrenia is a mental disorder characterized by alterations in cognition, behavior and emotions. Oral olanzapine (OZ) administration is extensively metabolized (~up to 40% of the administrated dose). In addition, OZ is a P-glycoproteins substrate that impairs the blood-brain barrier (BBB) permeability. To direct OZ to the brain and to minimize its systemic side effects, the nasal pathway is recommended. OZ-loaded polymeric micelles nano-carriers were developed using suitable biodegradable excipients. The developed micelles were physicochemically investigated to assess their appropriateness for intranasal delivery and the potential of these carriers for OZ brain targeting. The selected formula will be examined in vivo for improving the anti-schizophrenic effects on a schizophrenia rat model. The binary mixture of P123/P407 has a low CMC (0.001326% w/v), which helps in maintaining the formed micelles' stability upon dilution. The combination effect of P123, P407 and TPGS led to a decrease in micelle size, ranging between 37.5-47.55 nm and an increase in the EE% (ranging between 68.22-86.84%). The selected OZ-PM shows great stability expressed by a suitable negative charge zeta potential value (−15.11 ± 1.35 mV) and scattered non-aggregated spherical particles with a particle size range of 30-40 nm. OZ-PM maintains sustained drug release at the application site with no nasal cytotoxicity. In vivo administration of the selected OZ-PM formula reveals improved CNS targeting and anti-schizophrenia-related deficits after OZ nasal administration. Therefore, OZ-PM provided safe direct nose-to-brain transport of OZ after nasal administration with an efficient anti-schizophrenic effect.